Preparation method of sodium ion positive electrode binder
By introducing copolymer binders with embedded carboxyl groups into the sodium ion battery positive electrode binder, self-neutralization of alkaline residues, the problems of jelly-zination of the slurry of the sodium ion battery positive electrode material slurry and acid-base balance are solved, and the battery is improved Performance and productivity.
Patent Information
- Application Number
- CN202411611640.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-31
AI Technical Summary
The alkaline residue of the positive electrode material of sodium ion battery leads to jelly degradation of the slurry, affecting the coating effect and battery performance. The existing methods have problems such as difficulty in stabilizing the acid-base balance, additive residues and process complexity.
In the polymerization system of vinylidene fluoride monomers, an enoic acid monomer containing carboxyl groups is introduced, and a copolymer binder with embedded carboxyl groups is formed through copolymerization reaction, which self-neutralizes basic residues, avoids the addition of acidic additives, and simplifies Craft.
The stability of slurry fluidity and viscosity is achieved, the consistency of the electrode sheet coating and structural stability are improved, the cycle life and rate performance of the battery are extended, the production process is simplified, and the material purity is improved.
Smart Images

Figure CN119220204A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery positive electrode material preparation, and in particular to a method for preparing a sodium ion positive electrode binder. Background Art
[0002] Sodium-ion batteries have been widely used in energy storage systems and electric vehicles in recent years due to their abundant resources, low cost and stable performance. The positive electrode material usually uses O3-type layered oxides and uses polyvinylidene fluoride (PVDF) as a binder, which mainly plays the role of bonding active materials and conductive agents, thereby ensuring the mechanical strength and structural stability of the pole piece. However, the alkaline residues of sodium-ion positive electrode materials (such as NaOH and Na2CO3) easily react with CO2 and H2O in the air, causing the slurry to become jelly-like during the preparation process, reducing the fluidity of the slurry and making the viscosity unstable, affecting the coating effect of the pole piece and the final performance of the battery.
[0003] At present, in order to avoid the jelly problem of slurry, the industry usually adds carboxyl-containing organic acids (such as formic acid, acetic acid, etc.) to the positive electrode slurry to neutralize the alkaline residue in the slurry and inhibit the jelly effect. However, this method has the following disadvantages in practical applications: 1. The acid-base balance is difficult to stabilize: The amount of added organic acid must be strictly matched with the alkaline residue. However, in large-scale preparation, the alkaline residue is difficult to control accurately, and the acid-base balance is easily disturbed, resulting in large fluctuations in the slurry viscosity, affecting the preparation and coating effects of the slurry.
[0004] 2. Additive residue problem: The added organic acid may produce adverse by-products during the high-temperature formation stage, affecting the battery's internal resistance, cycle performance and high-temperature stability, and reducing the battery's long-term reliability.
[0005] 3. Complex process: The amount and timing of adding organic acid need to be precisely controlled, the process is complex, the production cost increases, and it is not conducive to large-scale mass production.
[0006] To overcome the above problems, the industry has also tried to stabilize the fluidity of the slurry by improving the slurry formula, introducing a variety of binder combinations, etc. However, these improvements have failed to fundamentally solve the problem of unstable acid-base balance, and may introduce more additives, resulting in a decrease in material purity, further affecting battery performance.
[0007] Therefore, how to realize the embedded neutralization function in the positive electrode binder of the sodium ion battery, simplify the process and improve the stability of the slurry has become a technical problem to be solved by the present invention. Summary of the invention
[0008] The technical problem solved by the present invention is to provide a method for preparing a sodium ion positive electrode binder in view of the defects existing in the above-mentioned prior art, so as to solve the problems of jelly formation and difficulty in stabilizing the acid-base balance of the sodium ion battery positive electrode slurry proposed in the above-mentioned background technology.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a sodium ion positive electrode binder, which is used to inhibit the jelly phenomenon caused by alkaline residue in the preparation of sodium ion battery positive electrode slurry, comprises the following steps: S1, introducing an olefinic acid monomer containing a carboxyl group into a polymerization system of a vinylidene fluoride monomer, so that the vinylidene fluoride and the olefinic acid monomer undergo copolymerization reaction to form a copolymer binder having a carboxyl group embedded in the molecular structure, wherein the molar content of the olefinic acid monomer is 0.001% to 0.1%, and the olefinic acid monomer includes acrylic acid, methacrylic acid or phenyl acrylic acid; S2, copolymerization is carried out by emulsion polymerization or suspension polymerization at a temperature of 60 to 120 degrees Celsius, a pressure of 1 to 5 MPa, and a reaction time of 8 to 20 hours, wherein the reaction system contains an initiator, an emulsifier or a dispersant to control the uniformity of the molecular structure; S3, the generated copolymer binder comprises a vinylidene fluoride group and a carboxyl group embedded therein in the molecular structure, wherein: The embedded carboxyl groups gradually release their neutralization function during the preparation and coating of the positive electrode slurry, reacting with the alkaline residual substances in the sodium ion positive electrode material, thereby maintaining the acid-base balance without the need for external acidic additives; The vinylidene fluoride group provides a bonding function, so that the binder has an enhanced effect in terms of slurry fluidity and viscosity stability to ensure coating consistency and structural stability of the pole piece.
[0010] As a further embodiment of the present invention, the initiator of the emulsion polymerization is persulfate, peroxycarbonate or diisopropyl peroxydicarbonate, and the amount used is 0.01% to 5% of the monomer mass; the emulsifier is sodium pentadecafluorooctanoate, and the amount used is 0.015% to 0.5% of the monomer mass.
[0011] As a further solution of the present invention, the dispersant of the suspension polymerization is methyl cellulose, the chain transfer agent is acetone, the conductivity of the deionized water solvent is less than or equal to 3 micro Siemens per centimeter, and the amount of the solvent is 1 to 20 times the mass of the monomer.
[0012] As a further embodiment of the present invention, the polymerization temperature during the reaction is preferably 75 to 90 degrees Celsius, and the polymerization pressure is preferably 2 to 4 MPa to ensure uniform distribution of the carboxyl groups in the molecular structure and their effective embedding.
[0013] As a further solution of the present invention, by introducing carboxyl groups during the synthesis of vinylidene fluoride, the carboxyl groups in the copolymer binder react with alkaline residual substances step by step during the slurry preparation process, without the need to add additional acidic components, thereby simplifying the slurry formula and improving the stability and purity of the slurry.
[0014] As a further solution of the present invention, the carboxyl-containing copolymer structure enables the binder to effectively neutralize the alkaline components in the sodium ion positive electrode material during the slurry preparation process to prevent the slurry from becoming a jelly and significantly improve the consistency of the electrode coating.
[0015] As a further aspect of the present invention, the bonding strength of the binder is improved by the embedded carboxyl groups, so that the required amount of binder is reduced to allow a higher proportion of active material to be filled for improving the specific energy of the battery and reducing the internal resistance.
[0016] As a further solution of the present invention, the dual-functional integrated design of the copolymer binder avoids the need for adding an external acid component and reduces residual impurities in the process by embedding the vinyl fluoride group and the carboxyl group into the same molecular structure.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. A built-in neutralization function is achieved, eliminating the need for external acidic additives: By introducing carboxyl groups into the vinylidene fluoride structure, the binder of the present application directly has the function of neutralizing alkaline residues at the molecular structure level, avoiding the need for traditional external organic acid additives, ensuring the automatic adjustment of acid-base balance during pulping, simplifying the formula, and maintaining stable fluidity of the slurry during stirring and coating, thereby inhibiting the jellying phenomenon.
[0018] 2. Embedded dual-function design improves process efficiency and material purity: The binder of this application greatly simplifies the production process by integrating neutralization and bonding functions. The embedded design of the carboxyl group avoids the problem of residual external components, reduces the potential impact of impurities on slurry and battery performance, makes the battery production process more efficient, and significantly improves the purity of materials, thereby improving the overall performance consistency of sodium-ion batteries.
[0019] 3. Enhanced bonding performance, improved battery specific energy and cycle life: Due to the introduction of carboxyl groups, this binder reduces the required amount while ensuring strong bonding, thereby increasing the filling ratio of active materials, effectively reducing the internal resistance of the battery, and improving specific energy. Experiments show that the use of this binder makes the pole piece structure more stable, significantly improves the pole piece peeling strength, extends the battery cycle life, and has better rate performance and long-term stability.
[0020] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 This is a performance comparison chart of the positive electrode slurry of the present invention.
[0023] Figure 2 This is a comparison chart of the viscosity of the positive electrode slurry of the present invention changing with time (unit: mPa•s).
[0024] Figure 3 This is a comparison chart of the density consistency of the positive electrode coating of the present invention (double-sided surface density g / m2).
[0025] Figure 4 This is a comparison chart of the peeling strength of the positive electrode sheet of the present invention.
[0026] Figure 5 It is a comparison chart of battery performance parameters of the present invention. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] See also Figure 1 —5. In an embodiment of the present invention, a method for preparing a sodium ion positive electrode binder is used to inhibit the jelly phenomenon caused by alkaline residue in the preparation of a sodium ion battery positive electrode slurry, comprising the following steps: S1, introducing an olefinic acid monomer containing a carboxyl group into a polymerization system of a vinylidene fluoride monomer, so that the vinylidene fluoride and the olefinic acid monomer undergo copolymerization reaction to form a copolymer binder having a carboxyl group embedded in the molecular structure, wherein the molar content of the olefinic acid monomer is 0.001% to 0.1%, and the olefinic acid monomer includes acrylic acid, methacrylic acid or phenyl acrylic acid; S2, copolymerization is carried out by emulsion polymerization or suspension polymerization at a temperature of 60 to 120 degrees Celsius, a pressure of 1 to 5 MPa, and a reaction time of 8 to 20 hours, wherein the reaction system contains an initiator, an emulsifier or a dispersant to control the uniformity of the molecular structure; S3, the generated copolymer binder comprises a vinylidene fluoride group and a carboxyl group embedded therein in the molecular structure, wherein: The embedded carboxyl groups gradually release their neutralization function during the preparation and coating of the positive electrode slurry, reacting with the alkaline residual substances in the sodium ion positive electrode material, thereby maintaining the acid-base balance without the need for external acidic additives; The vinylidene fluoride group provides a bonding function, so that the binder has an enhanced effect in terms of slurry fluidity and viscosity stability to ensure coating consistency and structural stability of the pole piece.
[0029] As a further embodiment of the present invention, the initiator of the emulsion polymerization is persulfate, peroxycarbonate or diisopropyl peroxydicarbonate, and the amount used is 0.01% to 5% of the monomer mass; the emulsifier is sodium pentadecafluorooctanoate, and the amount used is 0.015% to 0.5% of the monomer mass.
[0030] As a further solution of the present invention, the dispersant of the suspension polymerization is methyl cellulose, the chain transfer agent is acetone, the conductivity of the deionized water solvent is less than or equal to 3 micro Siemens per centimeter, and the amount of the solvent is 1 to 20 times the mass of the monomer.
[0031] As a further embodiment of the present invention, the polymerization temperature during the reaction is preferably 75 to 90 degrees Celsius, and the polymerization pressure is preferably 2 to 4 MPa to ensure uniform distribution of the carboxyl groups in the molecular structure and their effective embedding.
[0032] As a further solution of the present invention, by introducing carboxyl groups during the synthesis of vinylidene fluoride, the carboxyl groups in the copolymer binder react with alkaline residual substances step by step during the slurry preparation process, without the need to add additional acidic components, thereby simplifying the slurry formula and improving the stability and purity of the slurry.
[0033] As a further solution of the present invention, the carboxyl-containing copolymer structure enables the binder to effectively neutralize the alkaline components in the sodium ion positive electrode material during the slurry preparation process to prevent the slurry from becoming a jelly and significantly improve the consistency of the electrode coating.
[0034] As a further aspect of the present invention, the bonding strength of the binder is improved by the embedded carboxyl groups, so that the required amount of binder is reduced to allow a higher proportion of active material to be filled for improving the specific energy of the battery and reducing the internal resistance.
[0035] As a further solution of the present invention, the dual-functional integrated design of the copolymer binder avoids the need for adding an external acid component and reduces residual impurities in the process by embedding the vinyl fluoride group and the carboxyl group into the same molecular structure.
[0036] Embodiment 1: The positive electrode material of sodium ion battery is O3 type layered oxide, Na x MO2, where 0.67<x≤1, M is one or more transition metal elements such as Ni, Fe, Mn, Cu, Ti, CO, etc. The copolymer binder mainly includes two groups: Group 1 is PVDF obtained by polymerization of monomer VDF, and Group 1 is a polymer of unsaturated groups containing -COOH groups.
[0037] The molar content of -COOH unsaturated groups in the copolymer is 0.001-0.1%, preferably 0.002-0.02% Substances containing -COOH unsaturated groups include: acrylic acid, crotonic acid, methacrylic acid, methyl crotonic acid and other olefinic acids containing n carbon atoms; they can also be carboxylic acids containing phenyl groups, such as phenyl acrylic acid, phenyl crotonic acid, etc., olefinic acids containing functional groups such as hydroxyl groups, keto groups, and ether groups. Binder synthesis methods: emulsion polymerization, suspension polymerization, solution polymerization and supercritical polymerization, among which emulsion polymerization and suspension polymerization are preferred.
[0038] Emulsion polymerization mainly consists of monomers, deionized water, initiators, emulsifiers, and chain transfer agents; Suspension polymerization mainly consists of: monomer, deionized water, initiator, chain transfer agent and dispersant.
[0039] Initiator: persulfate, peroxycarbonate, tert-butyl hydroperoxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, the amount used is 0.01-5% of the monomer mass, preferably: 0.05-1.5%.
[0040] Solvent: deionized water, the conductivity of deionized water is ≤3μs / cm, the amount of solvent used is 1-20 times the mass of the monomer, preferably: 4-8 times.
[0041] Emulsifier: alkali metal salt of perfluorooctanoic acid, mainly sodium pentadecafluorooctanoate, lithium pentadecafluorooctanoate, potassium pentadecafluorooctanoate. The dosage is 0.015~0.5% of the monomer mass, preferably 0.1%~0.2%; Chain transfer agent: acetone, methanol, cyclohexane, isopropanol, etc., the amount used is 0.1%~10% of the monomer mass, preferably: 0.5%~5%.
[0042] Dispersant: Dispersants are generally cellulose ethers and polyvinyl alcohols, such as methyl cellulose and hydroxyethyl cellulose. The dosage is 0.01% to 5% of the monomer dosage, preferably 0.05% to 0.5%.
[0043] Synthesis temperature: the temperature of emulsion polymerization is 60℃-120℃, preferably: 75℃~90℃; the temperature of suspension polymerization is 20℃~80℃, preferably: 30~60℃.
[0044] Synthesis pressure: emulsion polymerization pressure: 1MPa~5MPa, preferably 2MPa~4MPa; suspension polymerization pressure: 1MPa~10MPa, preferably: 2MPa-8MPa; Synthesis time: emulsion polymerization time: 8-20h, polymerization time: 10-24h.
[0045] Positive electrode conductive agent: one or more of SP, ks-6, ks-16, C60, VGCF, CNTs slurry, etc.
[0046] Cathode solvent: NMP.
[0047] Negative electrode main materials: hard carbon, soft carbon, MoS, SnO2, titanium-based compounds; Negative electrode conductive agent: one or more of SP, ks-6, ks-16, C60, VGCF, CNTs slurry, etc.
[0048] Negative electrode binder: one or more of oily or water-based binders such as PVDF, PTFE, SBR, CMC, and PAA.
[0049] Anode solvent: NMP or water.
[0050] Diaphragm: PP, PE, PP / PE / PP, polyimide, acrylic and other diaphragms.
[0051] Core: stacked or wound.
[0052] Sodium ion battery forms: soft pack, cylindrical, aluminum shell, special shape, etc.
[0053] Comparative Example 1: Synthesis of PVDF binder: 1) Emulsion method: 100 parts of monomer VDF, 0.1 parts of emulsifier sodium pentadecafluorooctanoate, 0.1 parts of initiator diisopropyl peroxydicarbonate, 2 parts of chain transfer agent acetone, and 500 parts of deionized water are added to a reactor, stirred, and reacted at 80°C and 2.5MPa for 16 hours. After the reaction is completed, the synthesized emulsion is condensed, washed, separated, dried, and crushed to obtain a PVDF product; 2) Preparation of sodium ion batteries 1) 95 parts of NaNi O3 positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of PVDF synthesized by emulsion method, and 35 parts of solvent NMP, mixed evenly. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0054] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0055] Comparative Example 2: 1) Suspension method: add 100 parts of monomer VDF, 0.1 parts of dispersant methyl cellulose, 0.1 parts of initiator diisopropyl peroxydicarbonate, 2 parts of chain transfer agent acetone, and 500 parts of deionized water into a reactor, stir, and react for 20 hours at 50°C and 3.5MPa. After the reaction is completed, the synthesized suspension is centrifuged, washed, and dried to obtain the PVDF product; 2) Preparation of sodium ion batteries 1) 95 parts of NaNi O3 positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of PVDF synthesized by suspension method, and 35 parts of solvent NMP, mixed evenly. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0056] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0057] Method 1, synthesis of PVDF binder: 1) Emulsion method: 100 parts of monomer VDF and 0.005 parts of olefinic acrylic acid, 0.1 parts of emulsifier sodium pentadecafluorooctanoate, 0.1 parts of initiator diisopropyl peroxydicarbonate, 2 parts of chain transfer agent acetone, and 500 parts of deionized water are added to a reactor, stirred, and reacted at 80°C and 2.5MPa for 16 hours. After the reaction is completed, the synthesized emulsion is condensed, washed, separated, dried, and crushed to obtain a PVDF and polyacrylic acid copolymer product; 2) Preparation of sodium ion batteries 1) 95 parts of NaNi O3 positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of PVDF and polyacrylic acid copolymer synthesized by emulsion method, and 35 parts of solvent NMP, mixed evenly. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0058] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0059] Method 2: 1) Suspension method: 100 parts of monomer VDF, 0.01 parts of acrylic acid, 0.1 parts of dispersant methyl cellulose, 0.1 parts of initiator diisopropyl peroxydicarbonate, 2 parts of chain transfer agent acetone, and 500 parts of deionized water are added to a reactor, stirred, and reacted at 50°C and 3.5MPa for 20 hours. After the reaction is completed, the synthesized suspension is centrifuged, washed, and dried to obtain a copolymer product of PVDF and polyacrylic acid prepared by the suspension method; 2) Preparation of sodium ion batteries 1) 95 parts of NaNi O3 positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of PVDF and polyacrylic acid copolymer binder synthesized by suspension method, and 35 parts of solvent NMP, mixed evenly. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0060] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0061] Method 3: 1) Suspension method: 100 parts of monomer VDF, 0.01 parts of acrylic acid, 0.1 parts of dispersant methyl cellulose, 0.1 parts of initiator diisopropyl peroxydicarbonate, 2 parts of chain transfer agent acetone, and 500 parts of deionized water are added to a reactor, stirred, and reacted at 50°C and 3.5MPa for 20 hours. After the reaction is completed, the synthesized suspension is centrifuged, washed, and dried to obtain a copolymer product of PVDF and polyacrylic acid prepared by the suspension method; 2) Preparation of sodium ion batteries (low binder content, low battery internal resistance and high specific energy) 1) 95.5 parts of NaNi O3 type positive electrode material for sodium ion battery 1 / 3 Fe 1 / 3 Mn 1 / 3O2, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 1.5 parts of PVDF and polyacrylic acid copolymer binder synthesized by suspension method, and 35 parts of solvent NMP, mixed evenly. Determine the fineness, solid content, viscosity and viscosity stability of the slurry; apply it evenly on 12μm thick aluminum foil at a surface density of 150g / m2, and then roll it to roll the thickness of the pole piece to 120μm. 2) Mix 95 parts of hard carbon, a negative electrode material for sodium ion batteries, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water, measure the fineness, solid content and viscosity of the slurry, and evenly coat it on a 12μm thick aluminum foil at a surface density of 70g / m2, then roll it to roll the electrode sheet to a thickness of 167μm.
[0062] 3) The rolled positive and negative electrode sheets are cut and wound with a 12μm thick PE separator. After shelling, grooving, spot bottom welding, baking, liquid injection, cap welding, sealing, etc., they are then infiltrated, formed, and divided into different caps to obtain a sodium ion battery cylindrical battery.
[0063] Embodiment 2: This embodiment demonstrates the preparation method of the positive electrode binder for sodium ion batteries in the present application, and describes in detail the application process of the technical solution in terms of preparation, coating and battery performance, as well as its significant advantages over the prior art.
[0064] In the preparation of positive electrode materials for sodium-ion batteries, polyvinylidene fluoride (PVDF) is usually used as a binder to combine active materials, conductive agents and solvents into a slurry to achieve uniform coating and stable electrode structure. However, since alkaline residues in sodium-ion positive electrode materials such as NaOH and Na2CO3 easily react with moisture and carbon dioxide in the environment, the slurry often becomes jelly-like during the preparation process, reducing the fluidity and viscosity stability of the slurry, and seriously affecting the coating effect of the electrode. To solve this problem, the usual method is to neutralize the alkaline residue by adding carboxyl organic acids (such as acetic acid and formic acid), but this method has many problems in actual operation, including the difficulty in controlling acid-base balance, the adverse effects of residual additives on battery performance, and the complexity of the process.
[0065] The sodium ion positive electrode binder in this embodiment has a self-neutralizing function by embedding carboxyl groups in the vinylidene fluoride structure through improvements at the molecular structure level, thereby fundamentally suppressing the jellying phenomenon without the need for external organic acid additives.
[0066] The specific steps are: 1. Preparation of binder: Add carboxyl-containing acrylic acid monomer to the polymerization system containing vinylidene fluoride monomer to embed carboxyl groups in the vinylidene fluoride structure. Take vinylidene fluoride (PVDF) and acrylic acid, introduce acrylic acid at a ratio of 0.05% of the molar content of PVDF monomer, and copolymerize them under the reaction conditions of 80°C and 3 MPa by emulsion polymerization. Control the reaction by appropriate amounts of initiators and emulsifiers to obtain a copolymer binder with carboxyl groups embedded in the molecular structure, so that it has both bonding and neutralization functions in subsequent applications.
[0067] 2. Preparation and coating of positive electrode slurry: The prepared carboxyl copolymer binder, O3-type layered oxide sodium ion positive electrode material, conductive agent (carbon nanotubes) and solvent NMP are mixed evenly to form positive electrode slurry. In this process, due to the gradual reaction of the carboxyl groups embedded in the binder structure with the alkaline residues in the positive electrode material, the acid-base balance is automatically adjusted to ensure that the slurry has stable fluidity during the preparation process and avoid the jelly phenomenon caused by fluctuations in alkaline components. During the coating process, the slurry is evenly covered on a 12-micron thick aluminum foil, and the coating density is controlled at 150g / m². In the subsequent rolling operation, the thickness of the pole piece is controlled at 120 microns to keep the surface density of the coated pole piece consistent.
[0068] 3. Battery assembly and performance testing: The prepared positive electrode plate is assembled with the sodium ion battery negative electrode material (hard carbon) and the diaphragm to complete the injection, packaging and high-temperature formation steps. During the formation process, the carboxyl group in the binder does not produce harmful by-products, ensuring the stability of the electrode structure and the long-term cycle life of the battery. Compared with the traditional slurry with added organic acid, the binder of this embodiment enables the battery to have good internal resistance control, high capacity retention rate and excellent rate performance without introducing impurities. After 500 cycles, the battery capacity retention rate reached 95%, and the self-discharge rate after storage at a high temperature of 45°C for 7 days was less than 3%.
[0069] This embodiment achieves a direct solution to the jellying phenomenon of the slurry from the material structure through the self-neutralization function of the embedded carboxyl group. Compared with the traditional method of adding organic acid, this binder maintains a stable acid-base balance during the preparation and coating process, so that the positive electrode slurry can maintain the stability of fluidity and viscosity in multiple links such as slurrying, stirring and coating. In addition, since it does not contain added acidic components, the positive electrode slurry prepared by the binder of this application has no residual by-products, avoiding the impurity risk caused by added organic acid, thereby significantly improving the purity and electrochemical performance of the battery. This embodiment not only simplifies the production process in terms of technology, but also greatly improves the cycle life and rate performance of the battery, providing excellent technical support for the long-term stability and industrial application of sodium ion batteries.
[0070] Embodiment 3: In this example, a carboxyl-embedded vinylidene fluoride (PVDF) copolymer binder was synthesized by suspension polymerization and used in the preparation of positive electrode materials for sodium ion batteries to verify its effect on slurry stability and battery performance. Compared with the traditional method, this example avoids the addition of acidic additives, realizes the self-neutralization function through the improvement of the internal structure of the material, and improves the fluidity of the slurry process and the stability of the pole piece.
[0071] 1. Synthesis of copolymer binder: 100 parts of vinylidene fluoride (VDF) monomer and 0.01 parts of carboxyl-containing acrylic acid monomer are added to the reactor, and 0.1 parts of methyl cellulose as a dispersant, 0.1 parts of diisopropyl peroxydicarbonate as an initiator, 2 parts of acetone as a chain transfer agent, and 500 parts of deionized water with a conductivity of less than 3μs / cm are added. React for 20 hours at 50°C and 3.5MPa. After the reaction is completed, the resulting suspension is centrifuged, washed, and dried to obtain a PVDF and polyacrylic acid copolymer. The copolymer is embedded with carboxyl groups, so that the binder can gradually neutralize the alkaline residues in the sodium ion positive electrode material during the subsequent pulping process.
[0072] 2. Preparation and coating of positive electrode slurry: Mix the synthesized copolymer binder with 95 parts of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode material, 1 part SP conductive agent, 2 parts carbon nanotube (CNTs) conductive agent, and 35 parts NMP solvent are mixed and stirred to form a uniform positive electrode slurry. Through the embedded carboxyl group, the binder automatically neutralizes the residual alkali in the positive electrode material during the slurry preparation to avoid the jelly phenomenon of the slurry. The slurry is coated on an aluminum foil with a thickness of 12 microns, and the surface density is controlled to be 150g / m². After rolling, the thickness of the pole piece is controlled to be 120 microns. Through this process, the surface of the pole piece is uniform and the thickness is consistent, which meets the high-precision requirements of sodium-ion batteries.
[0073] 3. Battery assembly and performance testing: The positive electrode sheet is mixed with 95 parts of hard carbon negative electrode material, 1.5 parts of CMC thickener, 2 parts of SP conductive agent, and 2.5 parts of SBR binder to form the negative electrode sheet. The positive and negative electrode sheets and PE separator are wound and loaded into the battery shell. After the processes of liquid injection, packaging, formation and capacity division, the sodium ion battery is obtained. The test shows that the battery has significantly high stability and long life performance.
[0074] 4. Technical effect verification: This embodiment achieves the control of slurry stability and viscosity through material structure optimization. The surface density consistency of the pole piece after coating is significantly better than that of traditional binders. According to the test, the viscosity change of the slurry after standing for 24 hours is less than 5%, which effectively avoids the jelly phenomenon caused by alkaline residue. In addition, the capacity retention rate of the battery under 5C high-rate discharge conditions is 95.5%, and the capacity retention rate after 500 cycles is 97.9%, which has better high-rate and long-life performance than traditional PVDF binder batteries.
[0075] Embodiment 4: This example verifies the significant advantages of the binder of the present application in the positive electrode material of sodium ion batteries by comparing different samples in terms of positive electrode slurry stability, coating surface density, peel strength and overall battery performance. The following is a detailed analysis of the superiority of the technical solution of the present application in combination with each chart.
[0076] Table 1 - Comparison of cathode slurry performance.
[0077] Table 1 shows the performance comparison of the positive electrode slurry of different samples in terms of fineness, solid content, viscosity and jelly phenomenon. The traditional comparative samples (Comparative Example 1 and Comparative Example 2) showed jelly phenomenon during the preparation process, while Example 1 and Example 2 did not show jelly phenomenon, and the solid content and viscosity were at a stable level. This is because the binder of the present application has embedded carboxyl groups, which can gradually neutralize the alkaline residue during the slurry preparation process, thereby avoiding the loss of slurry fluidity and maintaining stable slurrying performance.
[0078] Table 2 - Changes in viscosity of cathode slurries over time.
[0079] Table 2 shows the viscosity changes of the positive electrode slurries of different samples at different time points. The viscosity of Comparative Example 1 and Comparative Example 2 increased significantly over time, and the viscosity exceeded the measurable range (>100000 mPa·s) after 24 hours, showing a jelly phenomenon. However, the viscosity of Example 1, Example 2, and Example 3 changed less, and the viscosity after 24 hours was maintained between about 9000 and 9900 mPa·s, showing excellent stability. This viscosity stability is attributed to the design of the embedded carboxyl group, which enables the binder to automatically adjust the acid-base balance during the slurrying process and effectively inhibit the jelly phenomenon.
[0080] Table 3 - Comparison of consistency of areal density.
[0081] Table 3 shows the consistency data of the positive electrode coating surface density. In the comparative samples, the surface density of each coating area varies greatly, ranging from 278 to 316 g / m², indicating uneven coating due to unstable viscosity. The surface density distribution of Examples 1, 2 and 3 is relatively uniform, and the fluctuation range is controlled between 295 and 304 g / m². This shows that the binder scheme of the present application enables the slurry to maintain good fluidity and stability during the coating process, thereby achieving uniform surface density distribution and improving the consistency of the pole piece.
[0082] Table 4 - Peel strength of positive electrode sheets.
[0083] Table 4 shows the peel strength of the positive electrode sheets of different samples. The peel strengths of Comparative Example 1 and Comparative Example 2 are 12.3 N / 25mm and 12.5 N / 25mm, respectively, while the peel strengths of Example 1, Example 2, and Example 3 are 15.7, 16.2, and 16.4 N / 25mm, respectively. This data shows that by embedding carboxyl groups, the binder of the present application not only has a neutralization function, but also enhances the bonding performance of the binder, thereby significantly improving the mechanical strength of the sheet, reducing the risk of sheet delamination, and improving the structural stability of the battery.
[0084] Table 5 - Battery performance comparison.
[0085] Table 5 shows the key performance of the battery, including internal resistance, initial charge and discharge capacity, rate retention rate, cycle life and specific energy. The capacity retention rates of the comparative samples at 5C rate are 93.4% and 93.6%, and the capacity retention rates after 500 cycles are 95.6% and 95.8%, respectively. In contrast, the 5C rate capacity retention rates of Example 1, Example 2 and Example 3 are 95.5%, 96.2% and 96.4%, respectively, and the capacity retention rates after 500 cycles are 97.1%, 97.5% and 97.9%, respectively. In addition, the specific energy of the example samples is significantly higher than that of the comparative examples, showing the efficient utilization rate of the materials. The present application scheme not only improves the cycle stability of the battery by optimizing the binder design, but also significantly reduces the internal resistance, improves the rate discharge performance and specific energy.
[0086] The data of this embodiment clearly demonstrates the application effect of the binder of this application in sodium ion batteries: first, by embedding carboxyl groups, the binder realizes the automatic adjustment of acid-base balance during pulping and coating, inhibiting the jelly phenomenon; second, the stable fluidity of the binder improves the consistency of electrode coating; third, the enhanced peel strength makes the electrode more durable and has better cycle performance. Overall, the technical solution of this application effectively improves the comprehensive performance of sodium ion batteries and provides reliable technical support for efficient and stable energy storage systems.
[0087] In the present invention, unless otherwise clearly stipulated and limited, the terms "installation", "setting", "connection", "fixation", "screw-on" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. Unless otherwise clearly defined, ordinary technicians in this field can understand the specific meanings of the above terms in the present invention according to the specific circumstances.
[0088] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a sodium ion positive electrode binder, which is used to inhibit the jelly phenomenon caused by alkaline residue in the preparation of sodium ion battery positive electrode slurry, characterized in that: The following steps are involved: S1, introducing an olefinic acid monomer containing a carboxyl group into a polymerization system of a vinylidene fluoride monomer, so that the vinylidene fluoride and the olefinic acid monomer undergo copolymerization reaction to form a copolymer binder having a carboxyl group embedded in the molecular structure, wherein the molar content of the olefinic acid monomer is 0.001% to 0.1%, and the olefinic acid monomer includes acrylic acid, methacrylic acid or phenyl acrylic acid; S2, copolymerization is carried out by emulsion polymerization or suspension polymerization at a temperature of 60 to 120 degrees Celsius, a pressure of 1 to 5 MPa, and a reaction time of 8 to 20 hours, wherein the reaction system contains an initiator, an emulsifier or a dispersant to control the uniformity of the molecular structure; S3, the generated copolymer binder comprises a vinylidene fluoride group and a carboxyl group embedded therein in the molecular structure, wherein: The embedded carboxyl groups gradually release their neutralization function during the preparation and coating of the positive electrode slurry, reacting with the alkaline residual substances in the sodium ion positive electrode material, thereby maintaining the acid-base balance without the need for external acidic additives; The vinylidene fluoride group provides a bonding function, so that the binder has an enhanced effect in terms of slurry fluidity and viscosity stability to ensure coating consistency and structural stability of the pole piece.
2. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: The initiator of the emulsion polymerization is persulfate, peroxycarbonate or diisopropyl peroxydicarbonate, and the amount used is 0.01% to 5% of the monomer mass; the emulsifier is sodium pentadecafluorooctanoate, and the amount used is 0.015% to 0.5% of the monomer mass.
3. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: The dispersant of the suspension polymerization is methyl cellulose, the chain transfer agent is acetone, the conductivity of the deionized water solvent is less than or equal to 3 micro Siemens per centimeter, and the amount of the solvent used is 1 to 20 times the mass of the monomer.
4. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: The polymerization temperature during the reaction is preferably 75 to 90 degrees Celsius, and the polymerization pressure is preferably 2 to 4 MPa to ensure uniform distribution of the carboxyl groups in the molecular structure and their effective embedding.
5. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: By introducing carboxyl groups during the synthesis of vinylidene fluoride, the carboxyl groups in the copolymer binder react with alkaline residual substances step by step during the slurry preparation process, without the need to add additional acidic components, thereby simplifying the slurry formula and improving the stability and purity of the slurry.
6. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: The carboxyl-containing copolymer structure enables the binder to effectively neutralize the alkaline components in the sodium ion positive electrode material during the slurry preparation process to prevent the slurry from becoming a jelly and significantly improve the consistency of the electrode coating.
7. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: The embedded carboxyl groups improve the bonding strength of the binder, reducing the required amount of binder to allow a higher proportion of active material to be filled for increasing the specific energy of the battery and reducing the internal resistance.
8. The method for preparing a sodium ion positive electrode binder according to claim 1, characterized in that: The dual-functional integrated design of the copolymer binder avoids the need for adding an external acid component and reduces residual impurities in the process by embedding the vinyl fluoride group and the carboxyl group into the same molecular structure.
Citation Information
Cited By
Vinylidene fluoride copolymer and preparation method thereof, positive electrode binder and sodium ion battery
CN120988178A